An oral SARS-CoV-2 M pro inhibitor clinical candidate for the treatment of COVID-19 - Owen, Dafydd R.; Allerton, Charlotte M. N.; Anderson, Annaliesa S.; Aschenbrenner, Lisa; Avery, Melissa; Berritt, Simon; Boras, Britton; Cardin, Rhonda D.; Carlo, Anthony; Coffman, Karen J.; Dantonio, Alyssa; Di, Li; et al. (Science (American Association for the Advancement of Science), 2021)
The rapid development of vaccines has been crucial in battling the ongoing COVID-19 pandemic. However, access challenges remain, breakthrough infections occur, and emerging variants present increased risk. Developing antiviral therapeutics is therefore a high priority for the treatment of COVID-19. Some drug candidates in clinical trials act against the viral RNA-dependent RNA polymerase, but there are other viral enzymes that have been considered good targets for inhibition by drugs. Owen et al . report the discovery and characterization of a drug against the main protease involved in the cleavage of polyproteins involved in viral replication. The drug, PF-07321332, can be administered orally, has good selectivity and safety profiles, and protects against infection in a mouse model. In a phase 1 clinical trial, the drug reached concentrations expected to inhibit the virus based on in vitro studies. It also inhibited other coronaviruses, including severe acute respiratory syndrome coronavirus 1 and Middle East respiratory syndrome coronavirus, and could be in the armory against future viral threats. —VV PF-07321332 is an orally active, small-molecule inhibitor of the SARS-CoV-2 main protease that is in clinical trials for the treatment of COVID-19. The worldwide outbreak of COVID-19 caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has become a global pandemic. Alongside vaccines, antiviral therapeutics are an important part of the healthcare response to countering the ongoing threat presented by COVID-19. Here, we report the discovery and characterization of PF-07321332, an orally bioavailable SARS-CoV-2 main protease inhibitor with in vitro pan-human coronavirus antiviral activity and excellent off-target selectivity and in vivo safety profiles. PF-07321332 has demonstrated oral activity in a mouse-adapted SARS-CoV-2 model and has achieved oral plasma concentrations exceeding the in vitro antiviral cell potency in a phase 1 clinical trial in healthy human participants.